PENGARUH TEKANAN FINANSIAL, ASIMETRI INFORMASI DAN KEPUASAN KERJA TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI PADA BANK PERKREDITAN RAKYAT (BPR) DI KOTA DENPASAR - Ni Made Kusumayanti; I Putu Nuratama; Putu Cita Ayu (Hita Akuntansi dan Keuangan, 2020)
Thei purpose ofi thisi study is to obtain empirical evidence about thei influence ofi financial pressures, informationi asymmetry andi job satisfactioni on thei tendencyi ofi accountingi fraud on thei Rural Credit Banki in Denpasarli City. Thei sample in thisi study was 20 rural banks in Denpasarli with 93 respondenits. Thei method ofi determiningi thei sample usingi purposivei sampling, datal collected by distributingi questionnaires. Datal were analyzed with Descriptivei Statistical Analysis, Validity Test, Reliability Test, Classic Assumptioni Test, F Test, t Test andi Multiple Lineari Regression Analysis. From thei results ofi thisi study, it can be seen that thei financial pressure variable has a positivei influence on thei tendencyi ofi accountingi fraud where a significancei value ofi 0.002 <0.05 is obtained, so thei higheri thei financial pressure, thei tendencyi ofi accountingi fraud is increasing. Thei informationi asymmetry variable has a positivei influence on thei tendencyi ofi accountingi fraud where a significancei value ofi 0.023 <0.05 is obtained so thei higheri thei informationi asymmetry, thei tendencyi ofi accountingi fraud is increasing. Thei variable job satisfactioni has a negativei influence on thei tendencyi ofi accountingi fraud where thei significancei value obtained is 0.818> 0.05 so thei higheri thei job satisfaction, thei tendencyi ofi accountingi fraud decreases.